Long-term Trial of Disodium Cromoglycate and Isoprenaline in Children with Asthma. Issue 5823 (12th August 1972) - Silverman, M.; Connolly, Nicola M.; Balfour-Lynn, L.; Godfrey, S.
Abstract : A year-long double-blind trial was carried out in 53 asthmatic children with severe perennial symptoms who were not receiving corticosteroids or corticotrophin. The treatment group were given disodium cromoglycate with isoprenaline (Intal Co.) while the placebo group were given lactose with isoprenaline four times daily. The groups were closely matched for clinical, physiological, and immunological features. Evaluation was based on the use of a diary and clinical and physiological investigations, including exercise tests. After one year 71% of the treatment group were still well controlled while 76% of the placebo group had dropped out because of inadequate control of symptoms. There was no rise in the rate of failure towards the end of the trial period and there were no seasonal variations in the failure rate. No important toxic effects were noted. It was impossible to predict the outcome of the trial in any given patient from his clinical, physiological, or immunological status at the beginning. However, the prevention of exercise-induced asthma by premedication with disodium cromoglycate in a laboratory exercise test did correlate well with the satisfactory clinical response to the drug.